1998
DOI: 10.5751/es-00037-020105
|View full text |Cite
|
Sign up to set email alerts
|

Climate and Tickborne Encephalitis

Abstract: Abstract•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…However, reliable data on TBE are available from some localized areas, for example from Stockholm County in Sweden where a surveillance programme ran for four decades after an outbreak in the late 1950s. Changes in incidence of TBE in the county during this time period have been shown to be related to changes in daily seasonal climate represented by "accumulated temperature days" (Lindgren, 1998;Lindgren & Gustafson, 2001). These TBE findings are of interest for the understanding of changes in LB prevalence as the incidences of both diseases show similar annual patterns, as shown in Fig.…”
Section: Observed Effects Of Recent Climate Variations In Europementioning
confidence: 78%
See 2 more Smart Citations
“…However, reliable data on TBE are available from some localized areas, for example from Stockholm County in Sweden where a surveillance programme ran for four decades after an outbreak in the late 1950s. Changes in incidence of TBE in the county during this time period have been shown to be related to changes in daily seasonal climate represented by "accumulated temperature days" (Lindgren, 1998;Lindgren & Gustafson, 2001). These TBE findings are of interest for the understanding of changes in LB prevalence as the incidences of both diseases show similar annual patterns, as shown in Fig.…”
Section: Observed Effects Of Recent Climate Variations In Europementioning
confidence: 78%
“…In some places this may be an effect of better reporting over time. However, studies from localized areas that have reliable long-term surveillance data show that such incidence increases are real, and that they are related to the same climatic factors that have been shown to be linked to changes in tick abundance (Lindgren, 1998;Lindgren & Gustafson, 2001;Daniel et al, 2004).…”
Section: Lyme Borreliosismentioning
confidence: 99%
See 1 more Smart Citation
“…Lindgren suggested that more ticks might survive in a mild winter in host and reservoir animals [17]. Due to an early arrival of the spring and/or late arrival of the next winter, ticks will be active for an extended period.…”
Section: Introductionmentioning
confidence: 99%
“…Further south, in areas with medium to high tick densities, further increases in tick abundance were related to a combination of milder winters (fewer days with minimum temperatures below 7 7 8C) and extended spring and autumn seasons (more days with minimum temperatures of 5^8 8C). Using the excellent national registration of TBE cases in Sweden since the 1950s, Lindgren (1998b) related the increase in TBE incidence from 1960 to 1995 in Stockholm County, a high-endemic region, to higher winter temperatures permitting a prolonged season of tick activity and hence pathogen transmission. Here the major increase occurred from 1984 onwards: 1960^1983, mean annual cases 18.6 (range 6^36); 1984^1995, mean annual cases 45.1 (range 33^74).…”
Section: Introductionmentioning
confidence: 99%